Proteolytic cleavage of amyloid precursor protein by ADAM10 promotes proliferation and migration via activating MAPKs pathway in tongue squamous cell carcinoma in vitro: ADAM10 cleaves APP to activate MAPKs pathway in TSCC - Hong, Yanqing; Wei, Zhuliang; Wang, Yunzhi (Cellular and Molecular Biology, 2023)
APP, well-studied in the development of Alzheimer's disease, has been recently identified as the key gene correlated with TSCC. Here, we investigate the function of APP and its proteolytic cleavage by ADAM10 in the pathogenesis of TSCC. A total of 63 TSCC patients and 30 healthy controls were included and the results of IHC assay showed high expressions of ADAM10 and APP in TSCC tissues compared to paired para-carcinoma tissues. Interestingly, APP expression in TSCC patients was correlated with ADAM10 expression and their combined expression was related to the poor patients' survival. We found that APP was ɑ-cleaved in TSCC cells to form sAPPα, and the serum level of sAPPα but not sAPPβ in TSCC patients was higher than healthy controls. Both overexpression with full-length APP and sAPPα promoted TSCC cell proliferation, migration and invasion. Downregulation of APP or ADAM10 by siRNA decreased the generation of sAPPα and inhibited the activity of ERK1/2 and p38 pathways, thereby reducing TSCC cell proliferation, migration and invasion. Treatment with ERK1/2 or p38 agonist or sAPPα overexpression reversed the effects of APP or ADAM10 knockdown. In conclusion, our data demonstrated the pathogenic roles of APP cleaved by ADAM10 to activate ERK1/2 and p38 pathways in TSCC cells. Both high expressions of ADAM10 and APP were related to poor prognosis. Targeting APP cleaved by ADAM10 might be a potential strategy in TSCC treatment.